2015
DOI: 10.1152/physrev.00007.2014
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Environment Interactions Controlling Energy and Glucose Homeostasis and the Developmental Origins of Obesity

Abstract: LBouret S, Levin BE, Ozanne SE. Gene-Environment Interactions Controlling Energy and Glucose Homeostasis and the Developmental Origins of Obesity. Physiol Rev 95: 47-82, 2015; doi:10.1152/physrev.00007.2014.-Obesity and type 2 diabetes mellitus (T2DM) often occur together and affect a growing number of individuals in both the developed and developing worlds. Both are associated with a number of other serious illnesses that lead to increased rates of mortality. There is likely a polygenic mode of inheritance u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(114 citation statements)
references
References 596 publications
(578 reference statements)
5
103
0
1
Order By: Relevance
“…Adverse nutritional and hormonal perinatal environments have been proposed to programme T2DM through inducing structural and functional alterations in key metabolic systems, including the brain, muscle, liver, adipose tissue and pancreas [1,[7][8][9]. During embryonic and foetal development, intense epigenetic remodelling is necessary to enable the establishment of transcriptional programmes associated with cellular proliferation and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Adverse nutritional and hormonal perinatal environments have been proposed to programme T2DM through inducing structural and functional alterations in key metabolic systems, including the brain, muscle, liver, adipose tissue and pancreas [1,[7][8][9]. During embryonic and foetal development, intense epigenetic remodelling is necessary to enable the establishment of transcriptional programmes associated with cellular proliferation and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, there have been many studies, particular animal studies that have verified this hypothesis and have demonstrated that malnutrition (both excess and deprivation) during pregnancy is associated with increased fat deposition in the offspring and may also directly impact the oocytes in females and primordial germ cells of male foetuses [20,21]. Furthermore, there is evidence that in utero over or under nutrition can affect DNA methylation, histone post-translational modification as well as gene expression of target genes involved in insulin signalling and fatty acid metabolism [22,23].…”
Section: Early Life Epigenetic Programmingmentioning
confidence: 99%
“…As adipose tissue is an endocrine organ that secretes substances (adipokines) that impact metabolism in other tissues, proteomic analysis of these factors is of interest. Human primary subcutaneous adipose tissue cells were cultured and tandem mass spectrometry used to analyse the secretome of the cells [21]. As well as the detection of a number of well-characterised adipokines-like adiponectin (validating the technique), this method leads to the identification of multiple serine protease inhibitors (called serpins) [21].…”
Section: Proteomic Changes In Human Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…epigenetic changes in the underlying metabolic tissues of the offspring that persisted after birth and result in permanent changes in the function of the gene [29].…”
Section: Journal Of Clinical Epigenetics Issn 2472-1158mentioning
confidence: 99%